Maximum Likelihood Symbol Timing Algorithm Based on Cyclic Prefix for OFDM Systems - Ibwe, Kwame (Tanzania Journal of Engineering and Technology, 2025)
In this paper, a blind symbol synchronization algorithm is presented for orthogonal frequency-division multiplexing (OFDM) systems, and a timing function based on the redundancy of the cyclic prefix (CP) is introduced. The existing algorithms rely on the prior knowledge of the channel energy distribution i.e. channel power profile. In practical environment the channel power profile is unknown to the receiver and its statistics are expected to be highly changing. Nevertheless, the use of pilot symbols in channel profile estimation reduces efficiency as data subcarriers are used to carry pilots instead of payload. In this paper a timing function that accounts for early and late timing introduced errors together with channel estimation errors is introduced. The effects of symbol timing errors are quantified and an optimal OFDM symbol timing solution is derived using modified maximum likelihood (ML) method. Compared with existing schemes in the literature, the proposed approach does not rely on explicit detection of individual channel paths or the delay spread boundary and therefore greatly reduces timing complexity. The main contribution lies in modifying the ML metric to jointly account for intercarrier interference (ICI), inter symbol interference (ISI), and channel estimation error, leading to improved robustness in dispersive channels without requiring prior channel knowledge. Simulation results show that the proposed algorithm is robust and outperforms the existing CP-based algorithms, particularly in double dispersive channels, achieving up to 5 dB NMSE improvement, lower BER at low SNR, and a 33% reduction in computational complexity.